Pengendalian Hipertensi pada Lansia Menggunakan Terapi Seduhan Bawang Dayak - Kurniawan, Didi; Zulfitri, Reni; Nopriadi, Nopriadi (Jurnal Kesehatan Komunitas, 2024)
Hypertension is a disease that can kill the sufferer silently (silent killer). The elderly most experience hypertension, as one of the effects of a decrease in the body's system so it requires non-pharmacological therapy to reduce polypharmacy in the elderly. The purpose of this study was to determine the effect of steeping Dayak onions on the function of controlling hypertension. The design of this study used a pre-experiment without a control group, namely one group pre-test-post-test design to determine whether there was an effect of giving Dayak onion steeping therapy in lowering blood pressure. Samples were taken using a purposive sampling technique totaling 38 respondents. The results of the data normality test showed that the data were not normally distributed, therefore the researcher used data analysis with the Wilcoxon Signed Ranks Test. The results showed that the Z value was smaller than the Z table value, so the Dayak onion steeping therapy affected decreasing blood pressure. Based on these conditions, Dayak onion infusion can be used as an additional therapy in controlling hypertension in the elderly.